Seul.es au monde ? Les jeunes adultes et la solitude pendant la pandémie - Cécile Van de Velde; Stéphanie Boudreault; Laureleï Berniard (Enfances, Familles, Générations, 2024)
Research framework: Young adults were the age group most affected by feelings of loneliness during the pandemic. To date, this phenomenon has mainly been approached by standardized mental health indicators: we argue that a sociological perspective can shed different light on these experiences.Objectives: Using a life-course approach, this article aims to understand the different meanings associated with experiences of loneliness during the pandemic, and to identify the social conditions that led to their occurrence. We highlight the main sources of loneliness among young people, the multiple emotions associated with it, and the different strategies for coping with it.Methodology: Our study is based on a comparative analysis of 48 life stories conducted in 2020 and 2021 with individuals aged 18 to 30, from various social backgrounds, in Montreal (16), Gaspé (16) and Toronto (16). Results: All the stories are initially marked by the existence of a “shock of loneliness”, but they are strongly polarized into three main experiences: loneliness as an “abyss”, as a “struggle” or as a “resource”.Conclusions: We cannot reduce the pandemic loneliness of young people to the suffering of isolation: in our study, young adults were affected by different types of loneliness - relational, but also existential and political - that are significant for their generation. We also show how precariousness tends to create a process of “cumulative loneliness”, and highlight the paradoxical role of social media on these different types of loneliness. Contribution: This article offers a better understanding of the social and generational factors behind the sharp rise in youth loneliness during the pandemic. It provides a better understanding of the dynamics of social inequalities in these experiences.